1994
DOI: 10.1007/bf00009496
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the number of bacteria added to soil or seeds and their abundance and distribution in the rhizosphere of alfalfa

Abstract: A study was conducted of the relationship between the density of several bacterial strains introduced into soil or onto seeds and their abundance in the rhizosphere of alfalfa. The abundance of six species in the rhizosphere was directly correlated with the density of bacteria initially added to soil. The density of six species in the rhizosphere of 15-day-old plants also was directly correlated with the density of each strain in nonrhizosphere soil. Tests of seven species added to soil at four inoculum densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Pseudomonas ST41 has many of the characteristics required to carry out this function and should be considered a candidate micro‐organism for further trials. However, Hatzinger and Alexander (1994) showed that single species inocula may be unreliable. A microbiological cocktail of native Antarctic hydrocarbon degrading bacteria with additional fertilization may be the best solution (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas ST41 has many of the characteristics required to carry out this function and should be considered a candidate micro‐organism for further trials. However, Hatzinger and Alexander (1994) showed that single species inocula may be unreliable. A microbiological cocktail of native Antarctic hydrocarbon degrading bacteria with additional fertilization may be the best solution (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Entrapment of bacteria in granular peat or polymer gels (32), optimization of the inoculum density (11), and pregermination of seeds (5) have been shown to improve root colonization by seed-associated bacteria. However, previous studies examining the importance of the presowing state have focused on individual strains, and knowledge of the root colonization capacity of broad bacterial groups is lacking.…”
mentioning
confidence: 99%
“…The antagonist survived well in rootfree sand after the suspension had been mixed into the sand (Kortemaa et al 1997). Hatzinger and Alexander (1994) showed that the bacteria which survived well in nonsterile soil were present in the highest population densities in the rhizosphere. Bahme and Schroth (1987) noted that the bacteria which survived in nonrhizosphere soil have good potential as biocontrol agents because the bacteria can await the emerging seed in the soil.…”
Section: Discussionmentioning
confidence: 99%